Determination of optimal transient in the anti-surge control system of the gas compressor unit - Семенцов, Георгій Никифорович; Лагойда, Андрій Іванович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper examines the problem of determining the optimal transient in the anti-surge control system of the gas compressor unit with gas turbine drive on the example of the C-6.3 type centrifugal supercharger. The problem of determining the switching points, constructing the optimal transient was considered. A method to improve the anti-surge control system performance in conditions of the booster compressor station of underground gas storage was proposed since performance of anti-surge control system of the gas compressor unit is a key factor to improve the booster compressor station reliability. The defined optimal transient in the anti-surge control system of the gas compressor unit with gas turbine drive and transient time show that they significantly differ from the transient in the system for the case when nonoptimal control action is supplied to the control object input.